Tiras cômicas na escola: multiletramentos no processo de ensino-aprendizagem de espanhol - Negreiros, Mary França (2021)
Due to the pandemic context, the challenge of Education, from the perspective of Critical Applied Linguistics (RAJAGOPALAN, 2006), in 2020, has been to rethink the use of technologies as teaching-learning instruments and development in the context of remote teaching. Thus, this study aims to investigate how social activities structured tasks (LIBERALI, 2012) supported by the Multiliteracy Pedagogy (NEW LONDON GROUP, 1996) enable learning and developing Spanish as an additional language (GARCÍA, 2009) within a seventh grade class of Elementary School in a private school virtual context. This research is grounded on Vygotsky ([1934] 2007; [1921-23] 1997) and Engeström (2008, 2011, 2013) when discussing the Socio-historical-cultural Activity Theory as part of the constitution of the human being. According to the authors, social participants develop through relationships organized by the language of argumentation that enables teaching-learning and Proximal Development Zones. Therefore, the Multiliteracy Pedagogy supports and organizes teaching-learning experiences and new ways of acting in the current world context of drastic and quick changes. When comparing this scenario of constant transformations, the comic strips (RAMOS, 2017) can be resources for discussion of the socio-historical-cultural moment, as they are widely used in textbooks and present multimodal language (ROJO; MOURA, 2012). In this context, the following research question arises: in which ways social activities structured tasks supported by the Multiliteracy Pedagogy and applied in a seventh-grade classroom of Elementary School enable or restrain the development of the participants Spanish? To answer this question, the Collaborative Critical Research organizes the look and actions of teacher-researcher and students regarding the use of Spanish through the critical development of reading and writing the text genre called comic strips, through data collected by screen recording during video calls of 40 minutes, once a week. The data were produced from August to September 2020 and evidence as research participants: the teacher-researcher, twenty-seven students, the coordinator, and a student's mother. The selection is organized to emphasize the situated practice, evident instruction, critical framing, and transformed practice relative to the different moments of teaching-learning concerning the Multiliteracy Pedagogy. The analyses are developed through performance (LIBERALI, 2009) and questions (NININ, 2018) focusing on the critical and collaborative development of the participants. As a result, we emphasize the importance of organizing the teaching-learning process of Spanish in a virtual environment to emphasize Multiliteracy and the experience of daily activities